Optimization of spray dried yogurt and its application to prepare functional cookies - Ali, Anwar; Javaid, Muhammad Tasawar; Tazeddinova, Diana; Khan, Ahmal; Mehany, Taha; Djabarovich, Toshev Abduvali; Siddique, Rabia; Khalid, Waseem; Tariq, Tayyaba; Lai, Wing-Fu (Frontiers in Nutrition, 2023)
Introduction Spray-dried yogurt powder (SDYP) has shelf stability and other functional properties that improve solubility and facilitate the use, processing, packaging, and transportation of other food derivatives, such as bread and pastries on a large scale. The present research was conducted to develop SDYP and further its utilization to prepare functional cookies. Methods Yogurt was spray-dried by employing different outlet air temperatures (OAT) (65°C, 70°C & 75°C) and inlet air temperature (IAT) (150°C, 155°C & 160°C). Spray drying shows that increasing the temperature increases nutritional loss, whereas S. thermophilus culture shows resistance to the intensive heat approaches. On the other hand L. delbrueckii subsp. Bulgaricus culture was found to be significantly affected. A total of 4 treatments, including one control for the functional cookies development. Results and discussion A directly proportional relation was investigated between the increasing concentration of SDYP and baking characteristics and cookie's mineral and protein profile. Bioactive parameters like antioxidant activity of 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH), 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid (ABTS) and total phenolic content (TPC) were also affected significantly. The sensory profile shows an incline towards T0 (0% SDYP) to T3 (10% SDYP) in all attributes but starts to decline when the concentration of SDYP reaches 15%. This study suggests that by employing a certain combination of temperatures (OAT: 60°C IAT: 150°C); maximum survival of inoculated culture can be achieved, and this powder can be utilized in the development of functional cookies with enhanced sensory as well as biochemical characteristics significantly (P< 0.05).